Synthesis of carbon nanotubes containing metal oxides and metals of the d-block and f-block transition metals and related studies - Chen, Y; Chu, A; Cook, J; Green, M; Harris, P; Heesom, R; Humphries, M; Sloan, J; Tsang, S; Turner, J (1997)
The filling of carbon nanotubes with metals and metal oxides via one- and two-step processes is presented. Both molten media and wet chemistry solution methods have been used to introduce foreign materials into the hollow nanotube cavities. Chemical reactions inside the tubes have been carried out, including the reduction of encapsulated materials to the metals. The nature of the crystalline filling has been found to be highly dependent on the techniques used. Wet chemical methods tend to result in filling which consists of discrete crystallites, whereas molten media methods tend to give long, continuous single crystals.